2001
DOI: 10.1007/s004210000327
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol and testosterone concentrations in wheelchair athletes during submaximal wheelchair ergometry

Abstract: It is yet unknown how upper body exercise combined with high ambient temperatures affects plasma testosterone and cortisol concentrations and furthermore, how these hormones respond to exercise in people suffering spinal cord injuries. The purpose of this study was to characterize plasma testosterone and cortisol responses to upper body exercise in wheelchair athletes (WA) compared to able-bodied individuals (AB) at two ambient temperatures. Four WA [mean age 36 (SEM 13) years, mean body mass 66.9 (SEM 11.8) k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…This is in accordance with some reports (Nieman et al 1995;Hakkinen et al 1998;Kraemer et al 1998b;Castellani et al 2001;Pullinen et al 2002;Goto et al 2005), in particular those which applied similar experimental protocols (Kraemer et al 1998b;Goto et al 2005). However, most studies on resistance exercise show an increase in cortisol levels (Kraemer et al 1987;Hakkinen and Pakarinen 1993;McMurray et al 1995;Ahtiainen et al 2003;Ramel et al 2003;Kokalas et al 2004;Tremblay et al 2004;Cadore et al 2008).…”
Section: Discussionsupporting
confidence: 90%
“…This is in accordance with some reports (Nieman et al 1995;Hakkinen et al 1998;Kraemer et al 1998b;Castellani et al 2001;Pullinen et al 2002;Goto et al 2005), in particular those which applied similar experimental protocols (Kraemer et al 1998b;Goto et al 2005). However, most studies on resistance exercise show an increase in cortisol levels (Kraemer et al 1987;Hakkinen and Pakarinen 1993;McMurray et al 1995;Ahtiainen et al 2003;Ramel et al 2003;Kokalas et al 2004;Tremblay et al 2004;Cadore et al 2008).…”
Section: Discussionsupporting
confidence: 90%
“…They also showed a higher exercise-induced increase in testosterone concentrations in subjects with disabilities. However, there were no differences in cortisol concentrations at rest as well as after exercise [ 30 ]. The physical mechanisms leading to an increase in exercise-induced testosterone levels are a result of both its production, breakdown, and excretion.…”
Section: Discussionmentioning
confidence: 99%
“…After these screening processes, thirteen studies met the inclusion criteria but one study was later excluded due to insufficient duration and environment to test the thermoregulatory capabilities. As a result, a total of twelve studies were included in this meta-analysis (Boot, Binkhorst, & Hopman, 2006;Castellani et al, 2001;Dawson, Bridle, & Lockwood, 1994;Fitzgerald, Sedlock, & Knowlton, 1990;Goosey-Tolfrey, Swainson, Boyd, Atkinson, & Tolfrey, 2008;Griggs, Havenith, Price, Mason, & Goosey-Tolfrey, 2017;Price & Campbell, 1997, 1999Theisen, Vanlandewijck, Sturbois, & Francaux, 2001;Trbovich, Ortega, Schroeder, & Fredrickson, 2014;Veltmeijer, Pluim, Thijssen, Hopman, & Eijsvogels, 2014;Zacharakis, Kounalakis, Nassis, & Geladas, 2013). A flow diagram of the screening process is presented in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…Effect size in this meta-analysis was calculated as the raw mean difference of core body temperature during exercise between persons with and without SCI. Among the included studies, two studies reported final measurement (cessation of exercise) core body temperature (Boot et al, 2006;Castellani et al, 2001); four studies reported change-from-baseline core body temperature (Dawson et al, 1994;Fitzgerald et al, 1990;Theisen et al, 2001;Zacharakis et al, 2013); three studies reported both final measurement and change-from-baseline core body temperature (Goosey-Tolfrey et al, 2008;Griggs et al, 2017;Trbovich et al, 2014); and three studies reported change-from-baseline core body temperature directly and presented figures of core body temperature responses, allowing indirect data extraction of final measurement core body temperature and correlation coefficients of change-from-baseline core body temperature to be calculated (see below) (Price & Campbell, 1997, 1999Veltmeijer et al, 2014). Considering baseline core body temperatures showed difference between experimental groups, the calculation of raw mean difference in this meta-analysis was based on change-from-baseline, when both final measurement and change-from-baseline data are available.…”
Section: Meta-analysismentioning
confidence: 99%